(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Agadatantra is one among the eight branches of Ayurveda deals with details of toxins, their effect on body and its management. Agadatantra has its roots in the Vedic period, where reference to poisons, especially snake venom, insect bites, plant-based toxins are mentioned. As per Ayurveda substance that rapidly spreads through the entire body is called Visha. Acharyas have divided Visha into two main types Sthavara (plant origin) and Jangama (animal origin) Visha. Mandali visha is one among the Jangama visha which needs proper management at time. Keraleeya visha chikitsa granthas possess abundant knowledge of practically used formulations in treatment of Visha as well as it’s complications. Kriya Kaumudhi a book written in Malayalam which explains about the treatment practices followed by Visha vaidyas from time to time. Sireesha panchanga yoga is explained in Mandalivisha prakaranam in Kriya koumadi. The use of this preparation in Mandali visha involves oral intake as Panam and topical application as Lepa. This yoga contains 8 ingredients, including Sireesha, Arka, Lodra, Vilwa, Haridra, Daruharidra and Manjista. The present article attempts to elucidate the potential mode of action of Sireesha Panchanga Yoga by assessing its pharmacological attributes and its effectiveness in treating Mandali Visha.